Extent of ST-Segment Depression Predicts In- Hospital Outcome in Non ST-Segment Elevation Acute Coronary Syndrome (Cardiovascular Journal, 2012)
Background: The presence of ischemic ECG changes on admission has been shown to predict outcome, the relationship between the extent of ECG changes and the risk of cardiac events is still ill   defined. The severity of ST-segment depression on admission ECG has a strong association with   adverse in-hospital outcome in patients with non ST-segment elevation acute coronary syndrome. The study was done to observe the extent of ST-segment depression and in-hospital outcome in patients with non ST-segment elevation acute coronary syndrome.   Methods: This study was conducted in the Department of Cardiology in NICVD Dhaka, from   January 2006 to December 2007. Considering inclusion and exclusion criteria, a total of 183 patients   were evaluated. All the patients were evaluated clinically after admission. ECG, blood biochemistry and echocardiography were done. Patients were categorized into three groups according to the extent   of ST- segment depression.   Results: In this study, analysis of the baseline parameters revealed no statistically significant   difference among the three groups of patients (p>0.05). Mean sum of the ST-segment depression analysis was done and all mean values were more in group III patients. 41.0% patients developed  complications during the study period. Acute LVF (22.9%) was the most common complication   followed by arrhythmia (11.5%), cardiogenic shock (4.4%) and STEMI (2.2%). All the complications were more in group III patients. During this period 6% patients died and more death (12.3%) was observed in group III patients.   Conclusion: The amount of ST-segment depression is a powerful predictor of adverse in-hospital   outcome in patients with non ST-segment elevation acute coronary syndrome DOI: http://dx.doi.org/10.3329/cardio.v5i1.12275 Cardiovasc. j. 2012; 5(1): 62-66